When to include clinical study reports and regulatory documents in systematic reviews - Jefferson, T; Doshi, P; Boutron, I; Golder, S; Heneghan, C; Hodkinson, A; Jones, M; Lefebvre, C; Stewart, L (BMJ Publishing Group, 2018)
Reporting bias is a major threat to the validity and credibility of systematic reviews. This article outlines the rationale for accessing clinical study reports and other regulatory documents (regulatory data) as a means of addressing reporting bias and identifies factors that may help decide whether (or not) to include regulatory data in systematic reviews. The article also describes the origins and current state of regulatory data access and summarises a survey of current systematic reviewers' practices in considering regulatory data for inclusion in systematic reviews. How to access and extract regulatory data is not addressed. Organisations and other stakeholders such as Cochrane should encourage the use of data from clinical study reports as an important source of data in reviews of pharmaceutical interventions particularly when the intervention in question is of high importance and the risk of reporting bias is great.